1996
DOI: 10.1055/s-2007-1015600
|View full text |Cite
|
Sign up to set email alerts
|

Klinische Relevanz der Mammographie beim Mann

Abstract: When malignancy is not suspected on clinical grounds the first examination should be sonography, mammography being reserved for cases of doubt. Where, however, malignancy is suspected, and for follow-up, mammography retains its primary position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2001
2001
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…On the basis of 104 mammograms in 89 men, Merkle et al. (1996) concluded that mammography is only necessary in rare cases, when malignancy is not suspected on clinical grounds.…”
Section: Mammographymentioning
confidence: 99%
“…On the basis of 104 mammograms in 89 men, Merkle et al. (1996) concluded that mammography is only necessary in rare cases, when malignancy is not suspected on clinical grounds.…”
Section: Mammographymentioning
confidence: 99%
“…Zusätzlich wurde die Symmetrie der Veränderungen evaluiert. Eine Vergröûerung der Brust durch Fettgewebe ohne den Nachweis von Parenchym wurde als Pseudogynäkomastie gewertet [10].…”
Section: Introductionunclassified
“…Für die statistische Auswertung wurden alle Läsionen der Typen 2 und 3 (scharf begrenzter Herdbefund) als benigne, die Typen 4 und 5 als maligne gewertet [10]. Die Sensitivität wurde definiert als rp/(rp + fn), der positive Vorhersagewert (ppv) als rp/(rp + fp), der negative Vorhersagewert (npv) als rn/(rn + fn) die Spezifität als rn/(rn + fp) und die Genauigkeit als (rp + rn)/ n [15].…”
Section: Introductionunclassified